Essential clinical anatomy - Moore, Keith Leon; Agur, Anne M R.; Dalley, Arthur F. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2015)
Essential Clinical Anatomy, Fifth Edition presents core anatomical concepts in a concise, student-friendly format. The text includes the hallmark blue Clinical Boxes, as well as surface anatomy and medical imaging features. It is an ideal text for shorter medical courses and health professions courses with a condensed coverage of anatomy. Essential Clinical Anatomy, like the authors' more comprehensive text, Clinically Oriented Anatomy, receives global acclaim for the relevance of its clinical correlations. The book emphasizes anatomy that is important in physical diagnosis for primary care, interpretation of diagnostic imaging, and understanding the anatomical basis of emergency medicine and general surgery. The 5th Edition features: a new and improved art program; illustrations have been redrawn in a modern, updated style that enhances student understanding of key concepts clinical boxes; renowned'blue boxes' highlight information on pathology, anatomical variation, trauma, the life cycle, surgical procedures, and diagnostic procedures surface anatomy and medical imaging; and chapters include surface anatomy and imaging sections to enhance clinical and diagnostic knowledge interactive review questions.
With bibliographical references and index.
1st edition: 1995.
This book includes online access at http://thepoint.lww.com/activate, please refer library staff for the password.
Keywords: Human anatomy; Anatomy; Atlases; Handbooks